2006
DOI: 10.1063/1.2167351
|View full text |Cite
|
Sign up to set email alerts
|

Large uniaxial magnetic anisotropy by lattice deformation in CoPt∕Ru perpendicular films

Abstract: A large uniaxial magnetic anisotropy Ku of about 2×107erg∕cm3 was obtained in Co–(20–30) at. % Pt perpendicular films deposited on Ru seed layers. The films showed good c-axis orientation perpendicular to the film plane, and no evidence of a Co3Pt-type-ordered structure was found in the X-ray-diffraction patterns. The value of Ku (the sum of the first- and second-order terms of uniaxial anisotropy, Ku1 and Ku2) increased as the thickness of the CoPt layer decreased, and reached about 2×107erg∕cm3 at 2 nm (Co–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…It is important to note that it is the growth fault probability, b, which is being shown, and the possible influence of b 0 cannot be determined from these figures. The most compelling correlation is the strong linear trend observed for K u versus c. Such a trend has been reported previously in the literature 21,22 and is qualitatively consistent with bulk measurements of magnetostriction for single crystal cobalt, where a compression …”
Section: -2supporting
confidence: 75%
“…It is important to note that it is the growth fault probability, b, which is being shown, and the possible influence of b 0 cannot be determined from these figures. The most compelling correlation is the strong linear trend observed for K u versus c. Such a trend has been reported previously in the literature 21,22 and is qualitatively consistent with bulk measurements of magnetostriction for single crystal cobalt, where a compression …”
Section: -2supporting
confidence: 75%
“…4) recorded in the plane (parallel) and out-of-plane (perpendicular) direction clearly show that the CoPt film deposited on Ru seed layer favors hcp phase formation resulting in higher perpendicular coercivity (H c = 1220 Oe) compared to the CoPt film depsited on Cu seed layer (H c = 254 Oe). This result is expected since it is known that a Ru underlayer exhibits an improvement of the microstructure and enhancement of perpendicular anisotropy of CoPt films obtained either by vacuum deposition 21,[24][25][26] or electrodeposition. 16,17,19,21 The dramatic improvement of crystal structure and perpendicular coercivity is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 80%
“…It has been reported that an hcp-CoPt (0 0 1) thin film grown on a Ru (0 0 1) buffer layer exhibits very high K u of the order of 10 7 erg/cm 3 [24,25]. This high K u of CoPt/Ru film does not require substrate heating during film deposition, and the crystal structure of the CoPt/Ru film is a disordered one.…”
Section: Copt/ru Dot Arraymentioning
confidence: 97%